Postoperative adjuvant hepatic arterial infusion chemotherapy with gemcitabine-cisplatin sequential capecitabine combined with PDL1 inhibitors in resected high-risk intrahepatic cholangiocarcinom: study protocol for a prospective, multicenter, single-arm, phase 2 trial (HgcCP trial) - Yang, Ying; Xie, Qing-Yun; Lv, Tao; Yang, Jiayin; Yu, Hai-Peng; Zheng, Xin; Zhang, Hui; Liu, Chang; Wu, Hong (Frontiers in Oncology, 2025)
BackgroundAlthough capecitabine is recommended for postoperative adjuvant treatment of biliary tract cancers (BTC), no studies have specifically focused on the postoperative adjuvant treatment of intrahepatic cholangiocarcinoma (ICC). In recent years, the combination of PD-L1 inhibitors and gemcitabine-cisplatin (GC) has demonstrated promising results in advanced BTC. The combination of GC, PD-L1 inhibitors, and capecitabine may be a potential adjuvant treatment for ICC. This phase II trial evaluates a novel regimen integrating hepatic arterial infusion chemotherapy (HAIC) with GC, sequential capecitabine, and PD-L1 inhibitors (HgcCP) for high-risk ICC after curative surgery.MethodsThis multicenter, single-arm trial enrolls ICC patients underwent radical surgery. Participants receive two cycles of HAIC with GC, followed by six cycles of capecitabine and eight cycles of PD-L1 inhibitor therapy. After completion of these therapies, patients will enter a 36-month follow-up period. The primary endpoints are recurrence-free survival (RFS) and safety; secondary endpoints include overall survival (OS) and time to recurrence (TTR).DiscussionThe HgcCP trial aims to establish a safe and effective adjuvant strategy for high-risk ICC after curative surgery, leveraging localized HAIC delivery and systemic immunotherapy. Results may guide future phase III trials.Ethics and trial registrationThis study has been approved by the Ethics Committee of West China Hospital of Sichuan University (IRB No. 2024-1982). The trial was prospectively registered at Chinese Clinical Trial Registry (http://www.chictr.org.cn, ChiCTR2500097319) on February 17, 2025.